The Influence of Fixed Asset Investment on Profitability (A study on PT. SEMEN TONASA in Pangkep Regency) - Sahade Sahade (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
This research aims to know the level the influence of invesment plant asset to profitability at PT. Semen Tonasa Regency Pangkep with the benefit expected result of to ratio analysis profitability can be made appliance of policy intake to always to pay attention to the its plant asset usage especially machine and factory equipments well so that continuitas company go well. This study is a quantitative research because the data of the research is quantitative data. The data are secondary data concerning financing, concerning Value of Invesment of Plant Asset and Profitability taken from finacial statement at PT. Semen Tonasa audit of which has audit during the year 2005-2009 which is obtained through documentation technique. The document are then analyzed by using profitbility ratio analysis (ROA) and linear regression. The result of the reserch shows that the result of profitability ration analysis of Return On Asset ( ROA) PT. Semen Tonasa experience of the very meaning improvement along with make-up of invesment value to plant asset of during five the last year namely year 2005 - 2009. While linear analysis result modestly to know that invesment plant asset have the influence which signifikan to profitability. Second the influence variable very strong namely be at the coefficient international 0,80 - 1,00, and level of the plant asset invesment the influence to profitability at PT. Semen Tonasa in Regency Pangkep equal to 85,6 percent.